A Study on Smart Parking System At AEON Seremban 2 - Zhe Min, Woo; Muslim, Rahmat (Progress in Engineering Application and Technology, 2022)
The literature review conducted in this study offers an in-depth review of common parking problems faced in shopping mall. On the other hand, it also offers an in-depth review of various types of smart parking system such as Parking Guidance and Information System (PGIS), transit based information system, smart payment system, e-parking, and automated parking system. Furthermore, the literature review shows the implementation of vehicle detection technologies into smart parking system. This paper presents a survey and analysis of an academic, qualitative literature review implementation process. It reviews many different types of smart parking system and analyse which is the best suits for AEON Seremban 2 through questionnaire which is prepared beforehand.